ETHICAL MANAGEMENT OF AI-PRODUCED DIGITAL WORKS - Dhavan, Dr. Avinash; Parmar, Yuvraj; Gupta, Shikha; Verma, Ashish; Agarwal, Varsha; Thangaraja T (ShodhKosh: Journal of Visual and Performing Arts, 2025)
he high rate of artificial intelligence (AI) innovation into the creative industries has transformed the creation of digital productions, upsetting the standard views of creativity, authorship, and ownership. The paper is an academic discussion on managing AI-generated digital literature on a multidisciplinary platform by looking at the convergence between technology, ethics, law, and society. It starts with its definition of AI-generated digital works and describes the existing technologies that allow machine-based artistic and intellectual works. Ethical issues that are core are examined, such as authorship, information privacy, disclosure, and responsibility. The paper also explores the legal loopholes in intellectual property rights, licensing, and regulatory differences in different countries, and suggests that there is an urgent necessity to harmonize the frameworks to apply the specifics of AI. Socioeconomic consequences are also evaluated, which includes the influence of AI on creative employment, the process of democratizing and monopolizing digital creativity, and the change in perception of authenticity and value in the population. In order to have ethical governance, the paper suggests elaborate frameworks that focus on ethical design, institutional responsibility and clear mechanisms of auditing. It proposes the implication of ethical factors in the lifecycle of AI developments, including data collection and implementation.